Alphaviruses in Gene Therapy - Lundstrom, Kenneth (Viruses, 2015)
Alphavirus vectors present an attractive approach for gene therapy applications due to the rapid and simple recombinant virus particle production and their broad range of mammalian host cell transduction. Mainly three types of alphavirus vectors, namely naked RNA, recombinant particles and DNA/RNA layered vectors, have been subjected to preclinical studies with the goal of achieving prophylactic or therapeutic efficacy, particularly in oncology. In this context, immunization with alphavirus vectors has provided protection against challenges with tumor cells. Moreover, alphavirus intratumoral and systemic delivery has demonstrated substantial tumor regression and significant prolonged survival rates in various animal tumor models. Recent discoveries of the strong association of RNA interference and disease have accelerated gene therapy based approaches, where alphavirus-based gene delivery can play an important role.